An Ecocritical Perspective on Agrarian Symbolism in “Mengantar Benih padi ke Ladang” - Sofyaningrum, Rosita; Zulaekhah, Dewi (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
This study explores the symbolic meanings of agrarian elements in Silvester Petara Hurit's short story Mengantar Benih Padi Terakhir ke Ladang to uncover the relationship between humans and nature through symbols such as rice seeds and fields. Employing a qualitative method and a descriptive-analytical approach, the research analyzes the short story's text and supporting literature to examine ecological perspectives, cultural values, and the conflict between agrarian traditions and modernity. The findings reveal that the short story represents agrarian symbols like rice, soil, trees, and life rituals as reflections of agrarian traditions, cultural identity, and the human-nature connection. The soil is portrayed as a metaphor for Mother Earth, while rice symbolizes life and the pride of agrarian communities. Additionally, the conflict between tradition and development reflects shifts in social values due to modernity. Agrarian symbolism in the story also highlights humanity's view of nature as a living entity with spiritual power while emphasizing the importance of maintaining ecological balance. This study significantly contributes to the understanding of agrarian symbolism in literature, particularly in the context of human-nature relationships, and offers a theoretical foundation for further studies on cultural and ecological dynamics in literary works. Abstrak Penelitian ini mengeksplorasi makna simbolik agraris dalam cerpen Mengantar Benih Padi Terakhir ke Ladang karya Silvester Petara Hurit untuk mengungkap hubungan manusia dengan alam melalui simbol-simbol seperti benih padi dan ladang. Dengan menggunakan metode kualitatif dan pendekatan deskriptif-analitis, penelitian ini menganalisis teks cerpen dan literatur pendukung untuk menggali pandangan ekologis, nilai budaya, serta konflik antara tradisi agraris dan modernitas. Hasil penelitian menunjukkan bahwa cerpen ini merepresentasikan simbol-simbol agraris seperti padi, tanah, pohon, dan ritual kehidupan sebagai refleksi tradisi agraris, identitas budaya, dan hubungan manusia dengan alam. Tanah diangkat sebagai metafora Ibu Pertiwi, sementara padi menjadi lambang kehidupan dan kebanggaan masyarakat agraris. Selain itu, konflik antara tradisi dan pembangunan mencerminkan perubahan nilai-nilai sosial akibat modernitas. Simbolisme agraris dalam cerpen ini juga mengungkapkan pandangan manusia terhadap alam sebagai entitas hidup dengan kekuatan spiritual, sekaligus menunjukkan pentingnya menjaga keseimbangan ekosistem. Penelitian ini memberikan kontribusi signifikan dalam memperkaya pemahaman tentang simbolisme agraris dalam sastra, khususnya dalam konteks relasi manusia dengan alam, serta menawarkan landasan teoritis untuk kajian lebih lanjut tentang dinamika budaya dan ekologis dalam karya sastra.